The Effects of Country Risk and Conflict on Infrastructure PPPs - Araya, Gonzalo; Schwartz, Jordan; Andres, Luis (World Bank, Washington, DC, 2013)
Through an empirical analysis of the relationship between private participation in infrastructure and country risk, the paper shows that country risk ratings are a reliable predictor of infrastructure investment levels in developing countries. The results suggest that a difference of one standard deviation in a country's sovereign risk score is associated with a 27 percent increase in the probability of having a private participation in infrastructure commitment, and a 41 percent higher level of investment in dollar terms. The predictive ability of country risk ratings exists for all sectors of infrastructure and for both greenfield and concessions. On average, energy investments exhibit a higher sensitivity to country risk than transport, telecommunications, and water investments. Concessions are more sensitive than greenfield investments to country risk, although country risk is a good predictor of investment levels for both contractual forms. Although foreign direct investment is found to be sensitive to country risk, the causal relationship is not nearly as sensitive as it is with private participation in infrastructure. Finally, an analysis of private participation in infrastructure patterns for those countries emerging from conflict reveals that conflict-affected countries typically require six to seven years to attract significant levels or forms of private investments in infrastructure from the day that the conflict is officially resolved. Private investments in sectors where assets are more difficult to secure--such as water, power distribution, or roads--are slower to appear or simply never materialize.